Shear rates in engines and implications for lubricant design. (September 2017) - Taylor, RI; de Kraker, BR
By combining shear rate range data in engine components with measured viscosity shear rate curves on lubricants (at different temperatures), useful insights have been obtained on how the viscosity shear rate curve of a lubricant should be "designed" to give low friction (and hence improved fuel economy). A brief review is carried out of typical shear rates in key engine components, which is backed up by the authors' own calculations (using in-house lubrication software that includes realistic viscosity/temperature/shear rate data). It is found that shear rates in journal bearings are typically in the range of 10 5 to 5 × 10 6 s −1, whilst peak shear rates for the piston rings can be as high as 2 × 10 7 s −1, and for the valve train, peak shear rates can reach 2 × 10 8 s −1 . Accurate viscosity shear rate curves have been measured for different temperatures using a range of viscometers, including a novel mid-shear capillary viscometer that is capable of measuring viscosities in the shear rate range of 10 4 to 10 6 s −1 . The use of such a viscometer is crucial to obtain good fits to the measured data (since usually, viscosity data are only usually available at low shear rates, 10 2 –10 3 s −1, and extremely high shear rates, > 10 6 s −1, and such data are difficult to use for accurate viscosity/temperature/shear rate fits). The implications of the above data are then discussed for the design of low friction lubricants which give improved fuel economy. It is highlighted that the traditional high temperature high shear viscosity, HTHS150, measured at 150 ℃ and a shear rate of 10 6 s −1, although adequate for bearing durability purposes, is probably not the ideal parameter to use for estimating the fuel economy potential of an oil (since shear rates in engines are usually much greater than 10 6 s −1, and also because oil temperatures in fuel economy engine tests are usually much lower than 150 ℃). Other possible high shear viscosity parameters are discussed which may be an improvement on HTHS150. The work also highlights that the choice of viscosity modifier, and the amount used, can have a substantial impact on the fuel economy performance of a lubricant.